2016
DOI: 10.1128/jvi.02704-15
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT-0 Component Hrs Promotes Macropinocytosis of Kaposi's Sarcoma-Associated Herpesvirus in Human Dermal Microvascular Endothelial Cells

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) enters human dermal microvascular endothelial cells (HMVEC-d), its naturalInteraction between Hrs and ROCK1 is essential for the ROCK1-induced phosphorylation of NHE1 (Na ؉ /H ؉ exchanger 1), which is involved in the regulation of intracellular pH. Thus, our studies demonstrate the plasma membrane association of ESCRT protein Hrs during macropinocytosis and suggest that KSHV entry requires both Hrs-and ROCK1-dependent mechanisms and that ROCK1-mediated phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Considering the implication of late endosomal components in LASV cell entry (31,35,36), it will be of interest to see if and at which point the macropinocytosis-related pathway described here merges into the classical late endosomal route. Interestingly, a very recent study revealed that cell entry of Kaposi's sarcoma-associated herpesvirus via macropinocytosis is promoted by Hrs, a component of the endosomal sorting complex required for transport, linking macropinocytosis to the multivesicular endosome (83) A targeted screen of kinase inhibitors of rLCMV-LASVGP entry, followed by suitable counterscreens, identified a set of specific candidates. The identified target kinases included PI3K and PKC, which are well-known to be involved in the regulation of macropinocytosis of many viruses and cellular cargo (12,64).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the implication of late endosomal components in LASV cell entry (31,35,36), it will be of interest to see if and at which point the macropinocytosis-related pathway described here merges into the classical late endosomal route. Interestingly, a very recent study revealed that cell entry of Kaposi's sarcoma-associated herpesvirus via macropinocytosis is promoted by Hrs, a component of the endosomal sorting complex required for transport, linking macropinocytosis to the multivesicular endosome (83) A targeted screen of kinase inhibitors of rLCMV-LASVGP entry, followed by suitable counterscreens, identified a set of specific candidates. The identified target kinases included PI3K and PKC, which are well-known to be involved in the regulation of macropinocytosis of many viruses and cellular cargo (12,64).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of in vitro KSHV infection have provided several pieces of novel information to virology research, such as the utilization of integrins for target cell infection by a herpesvirus (7), utilization of bleb-associated macropinocytosis for herpesvirus entry (4,15), c-Cbl playing an essential role in the bleb formation and macropinocytosis of KSHV (12,14), adaptor proteins CIB1, p130Cas, and Crk playing roles in macropinocytosis and trafficking of KSHV (12,14), and the association of cytosolic ESCRT Hrs protein with the plasma membrane and KSHV-containing macropinosomes (15). Current studies add to this list and demonstrate that ubiquitination of the KSHV receptors, integrin and EphA2R, by c-Cbl is recognized by the ESCRT-0 Hrs protein, which interacts with the virus-induced bleb region and virus-containing macropinosome (16).…”
Section: Discussionmentioning
confidence: 99%
“…KSHV infection induces the translocation of hepatocyte growth factor-regulated tyrosine kinase substrate (Hrs) protein, a prime component of the ESCRT-0 complex, to the plasma membrane near the KSHV-induced membrane blebs (15). This event is further amplified by the triggering of Rho-associated protein kinase 1 (ROCK1), which phosphorylates the sodium/hydrogen exchanger 1 (NHE1) to adjust a local pH change that is a critical step in macropinocytosis.…”
Section: Kshv Utilizes the Host Escrt Protein Complex For Entering Anmentioning
confidence: 99%
See 2 more Smart Citations